PENERAPAN VIDEO ANIMASI KARTUN UNTUK MENINGKATKAN HASIL BELAJAR OTK KEUANGAN KELAS XI SMKN 1 SURAKARTA - Fernanda Rizky Pratama; Patni ninghardjanti; Susantiningrum Susantiningrum (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2022)
This study aims to improve learning outcomes by using animated cartoon videos in class XI OTKP 3 SMK N 1 Surakarta OTK Finance subjects. This research is a classroom action research. The research was carried out in two cycles, each cycle consisting of planning, implementing actions, observing and collecting data, and reflecting. The subjects of this study were students of class XI OTKP 3 SMKN 1 Surakarta, totaling 34 children. Sources of data used come from teachers and students. Data collection techniques through observation, interviews, tests, and documents. Data validity uses source triangulation techniques, triangulation techniques, comparing data and concluding data. Data analysis used simple quantitative data analysis, qualitative data analysis, and comparative descriptive analysis. The results of the study indicate that learning outcomes can be increased by the application of animated cartoon videos. Based on data collected from pre-action, cycle I, and cycle II have increased, learning outcomes in pre-action as many as 5 students (14.7%) were declared complete, cycle I as many as 18 students (52.9%) were declared complete, and in the second cycle as many as 25 students (73.5%) were declared complete. Learning outcomes data were obtained from the results of the case test as many as 7 questions. The conclusion of this study is that the application of animated cartoon videos can improve learning outcomes of Financial OTK subjects in OTKP students of SMK N 1 Surakarta.